УЛОГАТА НА ЗЕМЈИТЕ ВО РАЗВОЈ ВО МЕЃУНАРОДНАТА ТРГОВИЈА (Yearbook - Faculty of Economics, 2018)
One of the most striking features of the global economy in recent years has been the increasingly large role played by developing economies. This paper examines the growing influence of developing countries in the global economy through the reduction of poverty, increased production and exports, in some cases eclipsing some of the industrialized economies. Trade flows of developing economies are also explored, focusing on the enhanced export opportunities for least-developed countries as a result of the trade opening of large, dynamic developing economies.